Visualizing near-field energy flow and radiation. - Miller, E.K (IEEE Antennas & propagation magazine.)
Computed near-field values of Poynting's vector and electric and magnetic field intensities for a linear dipole are displayed in a way that aids visualization of the radiation process. The fields are computed for time-harmonic excitation, but are shown as a function of time to demonstrate the spatial ebb and flow of the fields around the dipole. By this means, the distinction between near and radiation fields is made clearer, and the shedding of energy by the dipole can be observed.